Application of Handheld Tele-ECG for Health Care Delivery in Rural India. (28th September 2014) - Singh, Meenu; Agarwal, Amit; Sinha, Vineet; Manoj Kumar, Rohit; Jaiswal, Nishant; Jindal, Ishita; Pant, Pankaj; Kumar, Munish
Abstract : Telemonitoring is a medical practice that involves remotely monitoring patients who are not at the same location as the health care provider. The purpose of our study was to use handheld tele-electrocardiogram (ECG) developed by Bhabha Atomic Research Center (BARC) to identify heart conditions in the rural underserved population where the doctor-patient ratio is low and access to health care is difficult. The objective of our study was clinical validation of handheld tele-ECG as a screening tool for evaluation of cardiac diseases in the rural population. ECG was obtained in 450 individuals (mean age 31.49 ± 20.058) residing in the periphery of Chandigarh, India, from April 2011 to March 2013, using the handheld tele-ECG machine. The data were then transmitted to physicians in Postgraduate Institute of Medical Education and Research (PGIMER), Chandigarh, for their expert opinion. ECG was interpreted as normal in 70% individuals. Left ventricular hypertrophy (9.3%) was the commonest abnormality followed closely by old myocardial infarction (5.3%). Patient satisfaction was reported to be 95%. Thus, it can be safely concluded that tele-ECG is a portable, cost-effective, and convenient tool for diagnosis and monitoring of heart diseases and thus improves quality and accessibility, especially in rural areas.